The Digital Content: An Opportunity to Enjoy Collections - Corona, Lara (Mimesis Journal, 2024)
A major part of museum collections is not displayed, because it is kept in storage. As a consequence, collections are not available to people. One possible solution to enhance the accessibility of stored collections is to digitize them. Indeed, if digitized, all collections are potentially reachable by anyone, at any time, and everywhere. This article aims to highlight to what extent museums with archeological collections and those with historical items have embraced the digitalizing process to improve the accessibility of collections. Data were collected in thirty-one countries by disseminating a survey to the offices of the International Council of Museums (ICOM) and by direct invitations to museums. The study estimated that at least one item out of ten (70 percent of archeological and 75 percent of historical collections) was stored. The findings suggest that historical collections made available in the digital realm outnumber archeological collections two to one (42 percent and 21 percent of stored collections, respectively). The leading museums adopting the digital procedure are in Europe, as opposed to those with a slight degree of digitalization in Africa. The findings suggest that the museums with small collections digitize more stored items (77 percent for archeological museums and 57 percent for historical museums) than those with extensive collections (3 percent and 29 percent, respectively). Finally, the study underlines different channels through which collections are made accessible. Among them, social media (70 percent) prevail over the others, thereby allowing people to participate and interact with museums actively.